DISCLOSING TOTAL WAITING TIMES FOR JOINT REPLACEMENT: EVIDENCE FROM THE ENGLISH NHS USING LINKED HES DATA. (20th June 2013) - Marques, Elsa; Noble, Sian; Blom, Ashley W.; Hollingworth, William
ABSTRACT For the last decade, stringent monitoring of waiting time performance targets provided English hospitals with incentives to reduce official waiting times for elective surgery. It is less clear whether the total amount of time patients waited in secondary care, from first referral to outpatient clinic until treatment, has also fallen. We used Hospital Episode Statistics inpatient data for patients undergoing total joint replacement during a period of active monitoring of targets (between 2006/7 and 2008/9) and linked it to outpatient data to reconstruct patients' pathway in the 3 years before surgery and provide alternative measurements of waiting times. Our findings suggest that although official waiting times decreased drastically in our study period, total waiting time in secondary care has not declined. Patients with shorter official waits spent a longer time in a 'work‐up' period prior to inclusion in the official waiting list, and socio‐economic inequities persisted in waiting times for joint replacement. We found no evidence that target policies achieved efficiency gains during our study period. Copyright © 2013 John Wiley & Sons, Ltd.